Base Nacional Comum Curricular e currículo na educação infantil: uma proposta didático-pedagógica como possibilidade para prática docente no município de Bacabeira-MA - RABELO, Ana Karoline Pereira Wernz (2023)
This paper had on the study of the Early Childhood Education curriculum and the aspects of the Commom National Curriculum Base (BNCC) applied to it, having as its research location the Children’s Education Center Chapeuzinho Vermelho located in the municipality of Bacabeira-MA. The aim of this research is to propose a set of pedagogical guidelines for Children’s Education, by means of an E-book built from the reflection of the curriculum and, therefore, of the BNCC, in a collaborative manner with the teachers of the local schoolhouse, in order to re-signify and resize the curriculum. It is a qualitative research of pedagogical intervention, whose suggestions were debated from a training cycle, of which teachers of Early Childhood Education who exercise their functions in the classes of kindergarten I and II and the manager were the interlocutors. This research is grounded in several theorists and scholars, namely, Silva (2015), Lopes; Macedo (2011), Moreira; Silva (2013), more to legal documents in the early childhood education fieldin the field of curriculum, among others as Àries (1973), Kulhmann Jr (2015) and Sarat (2009) in the field of Early Childhood Education that were important to the theoretical support of this writing and decisive for the reach of our purposes. The study concluded that the research interlocutors, teachers and managers of the CEI Chapeuzinho Vermelho face a contrast as to the pedagogical practices and curriculum guided in the BNCC for Early Childhood Education that considers childhood in its totality. The results pointed out that the intervention process through the training cycle that discussed Early Childhood Education and the BNCC was very significant, since it gave possibility to the interlocutors experience training that allowed them to look into their classrooms.